Analisis Kadar LogamKadmium, Mangan dan Seng dalam Air Limbah secara Inductively Coupled Plasma - Optical Emission Spectrometry - Rauzatun Nusyura; Erni Azizah; Dewi Pujo Ningsih; Mubarokah Nuriani Dewi (Fakultas Teknik, 2023)
AbstractWastewater has the potential to cause water pollution which causes water quality to decrease due to imperfect sewage treatment, it can cause poisoning in fish and other aquatic biota both from organic waste and accumulation of inorganic heavy metals such as cadmium (Cd), manganese (Mn) and zinc (Zn). Control of water pollution is necessary so that the wastewater complies with the wastewater quality standards based on the Regulation of Permen Lingkungan Hidup RI No.5 (2014) Quality control of each test parameter is carried out by linearity test on wastewater, the value of linear regression correlation coefficient (r) on heavy metals is obtained. Cd, Mn, Zn were 0.9998; 0.9999; 0.9999. In the precision test of the wastewater test sample, the %RSD value was 2.01%, 5.21%, 2.58%. The %recovery values were 100.98%, 100.00%, 99.99%. The results of research showed the Cd, Mn and Zn metal using a spectrometer Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) Cd metal content in wastewater is 0.0070- 0.0504 (mg/L), Mn metal content is 0.0661 -0.9270 (mg/L), and Zn metal content 0.1823-1.1202 (mg/L). These results indicate that the metals Cd, Mn and Zn in wastewater samples compliance the quality standard classification of Permen Lingkungan Hidup RI No.5 (2014).keywords: heavy metals, ICP-OES, pollution, relative standard deviation, wastewater